Key Indicators in Analyzing the Sustainability of Afghanistan's Natural Resources - Fayaz Gul Mazloum Yar; Izat Ullah Sail; Shamsurahman Zahid; Aurelia Widya Astuti (Jurnal Syntax Transformation, 2024)
This study examines the factors affecting the sustainability of Afghanistan's natural resources, aiming to provide a framework for sustainable development and poverty alleviation. Using the Analytic Hierarchy Process (AHP) and strategic planning models, key factors such as organizational structure, management, economic, social, cultural, and ecological aspects were identified and prioritized. The findings indicate that organizational and managerial structure is the most critical factor, accounting for 38% of the overall importance. The research underscores the necessity for integrated and systematic management of natural resources to enhance economic and social well-being. It also emphasizes strategic planning, monitoring, and evaluation as essential components for effective resource management. A proposed model for sustainable natural resource management includes community empowerment, knowledge integration, economic viability, and improved communication among stakeholders. The study suggests that Afghanistan can develop its natural resources sustainably by leveraging strengths and opportunities while addressing weaknesses and threats. A comprehensive understanding of the various influencing factors and their interactions is vital for designing an effective model for sustainable management. This research contributes to the discourse on sustainable development in Afghanistan, providing actionable insights for policymakers and stakeholders in the natural resource sector.